(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The word culture is derived from the latin word ‘culturar’ means good manners and good taste. Culture is the sum total of human creations, expressions and experiences. It includes everything material and non-material created by man in the process of living. It is a kind of polished behaviour.